HUBUNGAN PENGETAHUAN DENGAN TINDAKAN PENCEGAHAN PENULARAN PADA KELUARGA PENDERITA TUBERKULOSIS PARU DI RUANG RAWAT INAP PARU RSUD ARIFIN ACHMAD PROVINSI RIAU - ", Nurfadillah; Yovi, Indra; Restuastuti, Tuti (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Pulmonary tuberculosis (TB) is an directly infectious disease caused by the bcateria Mycobacterium tuberculosis, which the transmission is through droplet in the air (droplet nuclei) when people with TB coughs or sneezes. Families who live at home with TB patients have a greater risk for contracting tb because can not avoid direct contact with TB patients. Prevention of transmission TB that can be done by family including, remind TB patients to shut the mouth every time when coughing or sneezing, remind TB patients to dispose of sputum in a special place that is closed, immediately check-up if there are symptoms of TB, open the window every day, sunning the and pillows regularly every day, maintaining personal hygiene and environment, consume the nutrisious food,etc. The research design was a cross sectional analytic and used the questionnaire as a research instrument, samples taken with accidental sampling techniqu, and the number of samples that included in inclusion criteria,were 30 samples, the results showed that the most respondents have good knowledge about pulmonary TB (56,7%), and most respondents did good precaution to pulmonary TB transmission (53,3%), and there is a relationship between knowledge with precaution pulmonary TB transmission, with siqnificancy= 0,04. So it can be concluded that the knowledge of pulmonary TB may affect precaution of pulmonary TB transmission.Key word :Tuberculosis (TB), knowledge, precaution.